2020
DOI: 10.1111/jog.14340
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity markers in endometrial mesenchymal stem cells of recurrent implantation failure and non‐recurrent implantation failure women: A pilot study

Abstract: Aim Endometrial mesenchymal stem cells (eMSC) have a vital role in regeneration of endometrium during menstrual cycles. Since it has been suggested that (eMSC) likely play a role in uterine receptivity and establishment of pregnancy, we aimed to evaluate the expression levels of five most known receptivity markers‐Integrin (ITG) β1, Rac1, HoxA11, ITGβ3 and Noggin‐in eMSC of recurrent implantation failure (RIF) and non‐RIF women. Methods Human eMSC were isolated from menstrual blood (MB) of RIF and non‐RIF wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Thus concluding that in this particular pilot study on determination of the expression levels of uterine receptivity markers in eMSC interestingly pointed that RIF and non-RIF eMSC were different regarding the expression of these markers. Future studies using these findings can brighten up more the role of eMSC in the endometrium receptivity and establishment of pregnancy [43].…”
Section: Introductionmentioning
confidence: 84%
“…Thus concluding that in this particular pilot study on determination of the expression levels of uterine receptivity markers in eMSC interestingly pointed that RIF and non-RIF eMSC were different regarding the expression of these markers. Future studies using these findings can brighten up more the role of eMSC in the endometrium receptivity and establishment of pregnancy [43].…”
Section: Introductionmentioning
confidence: 84%
“…In 2020, five markers of receptivity ( ITGβ1 [ 112 ], RAC1 [ 113 ], HOXA11 [ 111 ], ITGβ3 [ 112 , 114 ], and NOGGIN [ 111 ]) were compared between menstrual blood samples taken from women with RIF, versus fertile controls, revealing different patterns of expression. This observation led the authors to propose that aberrant eMSCs contribute to altered endometrial receptivity in women with RIF [ 115 ]. eMSCs from menstrual blood were isolated and characterised based on their morphology and behaviour, expression of specific surface markers (CD44, CD31, CD34, CD73, CD90, and CD105), and capacity to differentiate, all of which was based on the International Society for Cellular Therapy statement [ 115 , 116 ].…”
Section: Endometrial Stem/progenitor Cells and Recurrent Reproductive...mentioning
confidence: 99%
“…This observation led the authors to propose that aberrant eMSCs contribute to altered endometrial receptivity in women with RIF [ 115 ]. eMSCs from menstrual blood were isolated and characterised based on their morphology and behaviour, expression of specific surface markers (CD44, CD31, CD34, CD73, CD90, and CD105), and capacity to differentiate, all of which was based on the International Society for Cellular Therapy statement [ 115 , 116 ]. Notably, significantly higher expression levels of both HOXA11 and ITG β 3 were seen in the eMSCs of women with RIF [ 115 ].…”
Section: Endometrial Stem/progenitor Cells and Recurrent Reproductive...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that several molecules are expressed and silenced in the uterus during the peri-implantation period, which guides the sequential proliferation and differentiation of different cell types in the uterus (45,(53)(54)(55). Further analysis has shown that defects in uterine receptivity, such as failure of epithelial clearance and aberrant expression of uterine receptivity-related genes, are the main causes for implantation defects (56,57).…”
Section: The Role Of Endometrial Receptivity In Embryo Implantationmentioning
confidence: 99%